Pengembangan Klaster Agroindustri Di Desa Gondangan Kecamatan Jogonalan Klaten - Ida Susi D; Didik I; Asih Marini W (JURNAL ILMU SOSIAL, 2016)
SMEs snacks in Gondangan village has the potential to be developed. The village has the potential to be Gondangan Agro-industry region, although it is still much that needs to be repaired and prepared.This study aims to determine the attitude of the public about the development of SMEs in rural areas Gondangan into Agro-industry clusters and how community participation in the development of SMEs in rural areas Gondangan to be Agroindustri. Respondents in this study were the leaders and local community leaders, citizens, snack home industry in the region.This study is a descriptive study with a qualitative approach. The data of this study is primary data and secondary data consists of qualitative and quantitative data. Primary data were obtained with the interview and focus group discussion.The results showed that the attitude of the public, snack ho,e industri actor and local governments support the development of the region as an area of Agro-Industry cluster. In terms of participation, the government showed a high participation and support by facilitating a variety of activities to realize the region of Agro-Industry cluster, while the snacks businessman as the main actor of Agro-industry development of the area did not show a high level of participation.